Our old nursery rhymes - Moffat, Alfred; Willebeek le Mair, H. (Augener ; D. McKay, 1911)
An illustrated collection of traditional nursery rhymes with accompanying music.
Contains music.
An illustrated collection of traditional nursery rhymes with accompanying music.
Keywords: Nursery rhymes / 1911 / rbgenr